2016
DOI: 10.1097/inf.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Duration of Rhinovirus Infections in Children With Cystic Fibrosis and Healthy Controls

Abstract: This is the first in vivo longitudinal study showing that HRV is detected more frequently and persists for longer periods in CF patients compared with healthy controls. This might indicate increased viral replication and/or decreased antiviral defense in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
8
30
0
Order By: Relevance
“…The fact that, even in our study, the prevalence of HRV detection increased with older age in the CF group compared with healthy controls could already be an early sign of possible changes in the immune response or susceptibility to HRV, further leading to increased numbers of infections later in life. This is in line with a recent study,9 showing more frequent HRV detection in children with CF during respiratory infections and asymptomatic episodes compared with healthy controls 9. An additional indicator of different reactions to viruses already in early life might be the surprisingly high number of hBoV detection in our CF cohort.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that, even in our study, the prevalence of HRV detection increased with older age in the CF group compared with healthy controls could already be an early sign of possible changes in the immune response or susceptibility to HRV, further leading to increased numbers of infections later in life. This is in line with a recent study,9 showing more frequent HRV detection in children with CF during respiratory infections and asymptomatic episodes compared with healthy controls 9. An additional indicator of different reactions to viruses already in early life might be the surprisingly high number of hBoV detection in our CF cohort.…”
Section: Discussionsupporting
confidence: 93%
“…As expected in this young population, RV/EV remain the most frequently recovered viruses during RTI. Since the spread of molecular diagnostic tools, many studies have reported the same results in older children [1,4,6,9,15,25,26], adolescents and adults [3,10,11,15]. Overall, RV/EV are responsible for 70-80% of virally induced RTIs.…”
Section: Rti Epidemiology In Young Children With Cfmentioning
confidence: 89%
“…Whether or not this was the same subtype of picornavirus (RV or EV) was not addressed in this study, but prolonged carriage has been reported [4,29]. In a recent study conducted in a mean of Over the year of the study follow-up 3.5 years old (range, 0-17 years) CF patients population sampled weekly for 6 months, the authors found that patients with CF had a more frequent and prolonged carriage of RV in comparison to their healthy counterparts, even if the subtypes did not differ [4]. The authors conclude that "this may indicate increased viral replication and/or decreased viral antiviral defense in patients with CF."…”
Section: Rv/ev Carriagementioning
confidence: 99%
See 1 more Smart Citation
“…Some published evidence does not support the theory that pediatric patients with CF experience an increased incidence of laboratory-confirmed respiratory viral infections compared with healthy subjects, [19][20][21] while one recent study supports this theory. 22 Rather, it has been postulated that the increased prevalence of viral respiratory infections may be attributed to differences in the duration of infections (and the consequent duration of viral nucleic acid detection) due to a diminished specific antiviral defense [22][23][24] in patients with CF. 25 Furthermore, our 2 sensitivity analyses indicated that the RD estimate was robust to potential information bias from the diagnostic assays used to detect the presence of respiratory viruses.…”
Section: Discussionmentioning
confidence: 99%